Permission to parent : how to raise your child with love and limits - Berman, Robin E., 1950- (HarperWave, An Imprint of HarperCollinsPublisher, 2014)
Based on her clinical experience, a psychiatrist presents a valuable guide that helps parents and children navigate the emotional and psychological minefields of family dynamics.